Pemanfaatan ruang terbuka publik di Kampung Deret Petogogan Jakarta - Friska Hasibuan; Fermanto Lianto; Samsu Hendra Siwi; Martinus Bambang Susetyarto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
Currently, the existence of Kampung Deret Petogogan is due to the Jakarta government's work program, especially in the field of alleviating slum areas. In the past, this region was a slum area and it was the government's vision to transform it. Since 2013, it has been in a neat condition, not only for its occupancy, and also for its infrastructure in the open areas, which consist of parks and neighborhood roads. This research aims to determine the quality of public open spaces, such as parks and neighborhood roads for the residents. This study adopted descriptive qualitative methods, expected to benefit the government for the development of open spaces, and the community maintenance and utilization. The results showed that the democratic and beneficial aspects of the society, and the elements of quality public open spaces were achieved. Also, the productivity of open space utilization was very large. The element of responsiveness to physical and non-physical existence, and the need for infrastructure in an open space needs to be improved by maximizing its quality.